2018
DOI: 10.1016/j.bbmt.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Melphalan and Stem Cell Transplantation in Patients on Dialysis Due to Immunoglobulin Light-Chain Amyloidosis and Monoclonal Immunoglobulin Deposition Disease

Abstract: The kidney is the most common organ affected by immunoglobulin light-chain (AL) amyloidosis and monoclonal immunoglobulin deposition disease (MIDD), often leading to end-stage renal disease (ESRD). High-dose melphalan and stem cell transplantation (HDM/SCT) is effective for selected patients with AL amyloidosis, with high rates of complete hematologic response and potential for improved organ dysfunction. Data on tolerability and response to HDM/SCT in patients with ESRD due to AL amyloidosis and MIDD are limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 31 publications
(37 reference statements)
1
23
0
1
Order By: Relevance
“…Eligibility criteria for HDM/SCT vary between centers, but broadly require a confirmed tissue diagnosis of amyloidosis, clear evidence of a clonal plasma or B cell dyscrasia, and adequate measures of performance status (a grade of 0-2 at the ECOG performance status), cardiac function (a left ventricular ejection fraction of >40%, cardiac biomarkers below the thresholds, NewYork Heart Association class of <3), pulmonary function (O2 saturation >95% on room air), hepatic function (total bilirubin level <2 mg/dL) and hemodynamic stability (baseline systolic blood pressure >90 mm Hg). Patients on hemodialysis or peritoneal dialysis are not excluded at some centers if other eligibility criteria are met 89.…”
mentioning
confidence: 99%
“…Eligibility criteria for HDM/SCT vary between centers, but broadly require a confirmed tissue diagnosis of amyloidosis, clear evidence of a clonal plasma or B cell dyscrasia, and adequate measures of performance status (a grade of 0-2 at the ECOG performance status), cardiac function (a left ventricular ejection fraction of >40%, cardiac biomarkers below the thresholds, NewYork Heart Association class of <3), pulmonary function (O2 saturation >95% on room air), hepatic function (total bilirubin level <2 mg/dL) and hemodynamic stability (baseline systolic blood pressure >90 mm Hg). Patients on hemodialysis or peritoneal dialysis are not excluded at some centers if other eligibility criteria are met 89.…”
mentioning
confidence: 99%
“…In the context of renal impairment, certain drugs are preferred, such as cyclophosphamide and bortezomib that are better tolerated than melphalan and lenalidomide. Despite a limited response to melphalan and prednisone in light-chain deposition disease [48], a case series of four dialysis-dependent MIDD patients reported that high-dose melphalan followed by autologous stem cell transplant to be a safe and effective option that resulted in durable responses and subsequently allowed patients to receive a kidney transplant [49]. Many patients who develop end-stage renal impairment are often not considered for kidney transplantation due to their high rate of recurrence, as eradication of the underlying B-cell clone is not frequently possible [36][37][38].…”
Section: Monoclonal Gammopathy Of Renal Significance (Mgrs)mentioning
confidence: 99%
“…Risk factors for AKI included higher urine protein excretion, lower creatinine clearance at baseline, cardiac involvement, higher melphalan dose, and development of bacteremia during SCT [45]. HDM/SCT can also be safely and cautiously performed in patients with end-stage renal disease on dialysis and inducing durable hematologic responses then can make patients eligible for renal transplantation [46].…”
Section: Hdm/sct In Special Circumstances: In Patients With Renal Dismentioning
confidence: 99%